De olho no OPAC da biblioteca universitária: avaliação sobre e-acessibilidade e arquitetura da informação para Web com a interação de usuários cegos - Lazzarin, Fabiana Aparecida (2014)
Presents a focused study on aspects related e-Accessibility and Information Architecture (AI) for Web contained in online catalogs, also known as Online Public Access Catalogue (OPAC). The objective is to evaluate whether international accessibility guidelines and assumptions of AI are being contemplated. From the bibliographical project, resting on the exploratory and descriptive methods, we chose the case study as a research strategy. The analyzed sample is in the OPAC of the Management Academic Activities System (SIGAA) of the Federal University of Paraiba (UFPB). Involves the combination of qualitative and quantitative approaches, respectively, based on the verbal assessment of blind students with the OPAC and the automatic analysis of Web Accessibility. With the combination of scientific methods tool, carried out a triangulation between methods or intermethods capable to bring the holistic result expected for the phenomenon under study. It was concluded that the OPAC system SIGAA specifically UFPB, needs to pass through reformulations that meet international accessibility guidelines for Web, since it doesn t pass in the test battery with minimum level recommended by WCAG 2.0 document and in many respects was rated unfavorably by the research participants. Regarding the assumptions of AI for the Web that are contained in the OPAC , assessing that need to be better implemented in the environment , given that many participants found it difficult to interact with the OPAC as a result of informational complexity.